Screening of potential adipokines identifies S100A4 as a marker of pernicious adipose tissue and insulin resistance - Arner, Peter; Petrus, Paul; Esteve, David; Boulomié, Anne; Näslund, Erik; Thorell, Anders; Gao, Hui; Dahlman, Ingrid; Rydén, Mikael (INTERNATIONAL JOURNAL OF OBESITY, 2018)
Background Adipokines are peptides secreted from white adipose tissue (WAT), which have been linked to WAT dysfunction and metabolic complications of obesity. We set out to identify novel adipokines in subcutaneous WAT (sWAT) linked to insulin resistance (IR). Methods Gene expression was determined by microarray and qPCR in obese and non-obese subjects with varying degree of IR. WAT-secreted and circulating protein levels were measured by ELISA. Results In sWAT of 80 obese women discordant for IR, 44 genes encoding potential adipose-secreted proteins were differentially expressed. Among these, merely two proteins, S100A4 and MXRA5 were released from sWAT in a time-dependent manner (criterion for true adipokines) but only the circulating levels of S100A4 were higher in IR. In two additional cohorts ( n = 29 and n = 56), sWAT S100A4 secretion was positively and BMI-independently associated with IR (determined by clamp or HOMA-IR), ATP-III risk score and adipocyte size (hypertrophy). In non-obese ( n = 20) and obese subjects before and after bariatric surgery ( n = 21), circulating and sWAT-secreted levels were highest in the obese and normalized following weight loss. Serum S100A4 concentrations were higher in subjects with type 2 diabetes. S100A4 sWAT expression associated positively with genes involved in inflammation/extracellular matrix formation and inversely with genes in metabolic pathways. Although S100A4 was expressed in both stromal cells and adipocytes, only the expression in adipocytes associated with BMI. Conclusions S100A4 is a novel adipokine associated with IR and sWAT inflammation/adipocyte hypertrophy independently of BMI. Its value as a circulating marker for dysfunctional WAT and IR needs to be validated in larger cohorts.